2015
DOI: 10.1080/21645515.2015.1011954
|View full text |Cite
|
Sign up to set email alerts
|

A review of economic evaluations of 13-valent pneumococcal conjugate vaccine (PCV13) in adults and the elderly

Abstract: The 13-valent pneumococcal conjugated vaccine (PCV13) is already recommended for some adult groups and is being considered for wider use in many countries. In order to identify the strengths and limitations of the existing economic evaluation studies of PCV13 in adults and the elderly a literature review was conducted. The majority of the studies identified (9 out of 10) found that PCV13 was costeffective in adults and/or the elderly. However, these results were based on assumptions that could not always be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…4 Recent evidence has shown that PCV13 is efficacious against vaccine-type community acquired pneumonia, 5 which remains prevalent among older adults despite recently observed declines due to herd protection provided by use of PCV7 and PCV13 among children. 3,6 While previous studies have examined the cost-effectiveness of vaccinating old adults with PCV13, 7 this study fills a gap in the literature by incorporating clinical trial evidence of PCV13 effectiveness against community acquired pneumonia. We aimed to evaluate the marginal cost-effectiveness of the new recommendation as well as three alternate strategies to add PCV13 to the immunization schedule for adults.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent evidence has shown that PCV13 is efficacious against vaccine-type community acquired pneumonia, 5 which remains prevalent among older adults despite recently observed declines due to herd protection provided by use of PCV7 and PCV13 among children. 3,6 While previous studies have examined the cost-effectiveness of vaccinating old adults with PCV13, 7 this study fills a gap in the literature by incorporating clinical trial evidence of PCV13 effectiveness against community acquired pneumonia. We aimed to evaluate the marginal cost-effectiveness of the new recommendation as well as three alternate strategies to add PCV13 to the immunization schedule for adults.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy assumed for PCV13 against vaccine-type non-bacteremic pneumococcal pneumonia in these analyses tended to be higher than subsequently found in the CAPiTA trial. 21 Likewise, the proportion of all pneumonia assumed to be caused by pneumococcus was often relatively high (30%-40%) 21 when compared to some recent data. 35 To reliably inform vaccine policy, new economic evaluations are required that use the best data now available, particularly the CAPiTA trial data and up-to-date data on the evolving serotype-specific disease burden in each setting.…”
mentioning
confidence: 98%
“…The lack of reliable data on this outcome for PPV23 is unfortunate, as the relative efficacy assumed for each vaccine against non-invasive pneumonia (particularly cases resulting in death) is very influential when estimating their cost-effectiveness. 21 The duration of vaccine-induced protection is likely to be equally important in estimating the cost and benefits of alternative pneumococcal vaccines. Most economic evaluations have evaluated the use of the vaccines in older adults of various ages under 75 years, 21 as the very old are more likely to have reduced immunogenicity to vaccination.…”
mentioning
confidence: 99%
See 2 more Smart Citations